Satisfactory Level with LIC’s Service - Dr.R.Indirajith, S.Maheswari, (International Journal of Scientific Research and Management (IJSRM), 2017)
The current scenario in the insurance industry is a complex and competitive environment tinged with little stability. The success of the insurance business depends on the awareness of the policy holders about the products and satisfaction of the policy holders regarding the service rendered by LIC of India. As per the instruction, given by IRDA the LIC of India opened branches in rural semi urban and urban areas. There are eighteen branches in division. The researcher has selected all these branches for this study. Insurance industry is a service-oriented unit. It renders services like sufficient space, display adequate information, suggestion box, timely intimation about premium, immediate premium receipt, coverage of risk etc. The study revealed that in general, all the respondents/policy holders have certain level of expectations from the services that are to be delivered by an insurance company. Their expectation level varies irrespective of the demographic profile (such as gender, age, etc.). The forthcoming years will be more dynamic and challenging among the insurance companies as delivering excellent services to all the strata of the economy will ensure their share.